Kinerja Birokrasi Bidang Sarana dan Pelaku Distribusi dalam Meningkatkan Kualitas Pelayanan Dinas Perindustrian dan Perdagangan - Anggraini, Vera Dian; Hartono, Budi; Budiani, Ina Triesna (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study is to discuss the performance of the bureaucracy and the efforts made by the Facilities and Distribution Actors in improving the quality of service at the Department of Industry and Trade of Deli Serdang Regency. This type of research is qualitative research that uses descriptive qualitative research methods. Data collection techniques are carried out by conducting field research by conducting interviews and library research with document studies. Data analysis in this study used qualitative data analysis. The results showed that the performance of the bureaucracy in the field of facilities and distribution actors in improving service quality, especially in managing the Bakaran Batu market, had not been able to achieve the performance target. Employee performance has not shown good quality, quantity of performance. So that there is a failure to realize the vision and mission of the organization, which has an impact on the low quality of service to the community. Efforts are being made to improve the Bureaucratic Performance in the Field of Facilities and Distribution Actors in order to improve the quality of service at the Department of Industry and Trade of Deli Serdang Regency, by increasing resources, including human resources. Improving responsiveness, responsibility and accountability in implementing employee performance, also requires evaluation in problem-solving related to the lack of interest of traders to trade in the Bakaran Batu market.